The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fcosc.2022.991765
|View full text |Cite
|
Sign up to set email alerts
|

How did the deer cross the fence: An evaluation of wildlife-friendlier fence modifications to facilitate deer movement

Abstract: Fences are a common feature throughout the landscape of North America’s Great Plains region. Knowledge surrounding the harmful implication that fences have on the movement of wildlife, specifically ungulates, is expanding. Across the region, it is accepted that there is a need to mitigate the impacts of barbed wire fencing and that “wildlife-friendlier” fence designs are emerging as a practical tool to meet these goals. Here we evaluate the response of sympatric deer species to the implementation of two fence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In addition, the allocation of funds to expand this land base via restoration practices (Downey et al, 2013) will be required, as this landscape is home to many declining species for which their currently available habitats fail to produce the templates necessary for recovery. Finer-scale products could help guide practitioners to areas for implementing projects demonstrated to alleviate known threats to species (e.g., MacDonald et al, 2022). Ultimately stakeholders need to be equipped by strategically identifying key landscapes for protection, and 'chipping away' with limited funds and opportunities on incentive-based conservation over long-term investments.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the allocation of funds to expand this land base via restoration practices (Downey et al, 2013) will be required, as this landscape is home to many declining species for which their currently available habitats fail to produce the templates necessary for recovery. Finer-scale products could help guide practitioners to areas for implementing projects demonstrated to alleviate known threats to species (e.g., MacDonald et al, 2022). Ultimately stakeholders need to be equipped by strategically identifying key landscapes for protection, and 'chipping away' with limited funds and opportunities on incentive-based conservation over long-term investments.…”
Section: Discussionmentioning
confidence: 99%
“…In areas of rewilding, barriers are needed to keep the large grazers in an enclosure to prevent conflicts between humans and animals [5,6]. These barriers are often physical, such as electric fences or sisal ropes, which can be an obstacle for the local wildlife as it restricts their migration and is not fit for quick alterations [5,[7][8][9].…”
Section: Of 18mentioning
confidence: 99%
“…These barriers can also lead to collisions, such as when low-flying bird species collide with fences with lethal consequences [3,[6][7][8][9]. An example of an affected species, which are comparable in size and ecology to native European red deer and fallow deer, are the North American white-tailed deer and mule deer, as described by Harrington et al, Burkholder et al and Bishop et al [7,10,11]. These papers found that deer were prone to getting caught and dying when attempting to cross fences, with fence crossing success rates at around 75% and mortality rates upwards of 0.40/km/year for pasture fences [7,11].…”
Section: Introductionmentioning
confidence: 99%